Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1556/aphysiol.101.2014.009
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of peak power output during a 10-s cycling maximal effort using different sampling rates

Abstract: 29Aristides Machado-Rodrigues [rodriguesari@hotmail.com] The study was aimed to investigate the reproducibility of performance parameters obtained 4 from 10-s sprints against different braking forces in young adult athletes. The sample (n=48) 5 included male athletes aged 18.9-29.9 years (175.5±6.9 cm, 76.2±10.1 kg). The 10-s 6 maximal exercise was performed in a cycle-ergometer against a random braking force (4% to 7 11% of body mass). Intra-individual variation was examined from repeated tests within one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Most studies of cycling power in children and in adults have used the popular 30-s WAnT. Few authors have reported the reproducibility of PP output measurements [ 5 , 14 ]. This study hypothesized that maximal cycling power computed from the OL derived from the parabolic relationship between Fb and power output does not require a familiarisation session.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies of cycling power in children and in adults have used the popular 30-s WAnT. Few authors have reported the reproducibility of PP output measurements [ 5 , 14 ]. This study hypothesized that maximal cycling power computed from the OL derived from the parabolic relationship between Fb and power output does not require a familiarisation session.…”
Section: Discussionmentioning
confidence: 99%
“…Results confirmed that estimated PP-OL obtained from the FVT protocol seemed to be reasonable reproducible in adult non-elite athletes. A previous study [ 5 ] examined reproducibility of 10-s PP measured in cycling effort against different Fb’s in male young adult athletes (n = 48) and reported a TEM of 59 Watt (%CV = 5.52%; ICC = 0.951, 95% CI: 0.912; 0.972). Early studies using the WAnT recommended the determination of PP output over a 5-s period and assumed that this would reflect alactic anaerobic performance [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations